Seasonal and Diel Patterns of Total Gaseous Mercury Concentration In Atmospheric Air of the Central Valley of Costa Rica - Castillo, Aylin (2011)
Monitoring mercury in atmospheric air near volcanoes is limited with no previous data for Costa Rica. Seasonal and daily patterns of total gaseous mercury (TGM) were observed at our main sampling location at the Universidad Nacional, Heredia, Costa Rica. The area (lat 10.000230 long -84.109499) is located in the Central Valley of Costa Rica and is 27 km south-east of the Poas volcano (lat 10.199486 long -84.231388). Measurements were made from May 2008 to May 2009 at this location with some additional values obtained at other sites near the Poas volcano including San Luis and Grecia as well as the, Turrialba and Irazu volcanoes. Total gaseous mercury (TGM) was determined in samples collected at a height of 2 m using the Tekran 2537A (Tekran Inc.) gas-phase mercury vapor analyzer. Meteorological data (temperature, relative humidity, wind speed, wind direction, radiation, and precipitation) were obtained from the airport weather station located at Alajuela. Monthly precipitation is typically 85 mm during the dry season (December to April) with winds from the west. The wet season begins in late April and continues to December with monthly rainfall of 328 mm and winds from the north east. The annual mean temperature is 20 degrees C. With the onset of the wet season TGM increased from typical values near 10 to 905 ng m-3. Measurements made within 5 km from the Poas volcano were higher than at Heredia at that time. Diel values measured at the university site increased until midday along with temperature and radiation. Relative humidity showed a reciprocal pattern. We observed that high values of TGM were not related to wind velocity or direction. The strong diel pattern increased with sunrise, peaked at midday and was lowest during the night time. It would seem that elemental mercury from the volcano is oxidized and is deposited to the soils during the dry season when winds are blowing from the volcano. With the onset of heavy rains in April, mercury in the soil is reduced and re-volatilized resulting in the high levels in atmospheric air. Values at other volcano sites were provided. The role of atmospheric pollutants such as hydrogen peroxide and ozone should be included in future studies as they may result in oxidation of reduced mercury. The instability in the air masses may also be a factor and local pollution sources may result in high levels of mercury being circulated to ground level as radiation intensity increases.